Engineering the Channel Tunnel - Kirkland, Colin J. (Chapman & Hill, 1995)
The Channel Tunnel may be the greatest engineering project in Europe this century. This book describes the tremendous engineering achievement of the construction of the tunnel. Written by twenty of the key engineers involved, it provides a fascinating, informative and inspiring account of the project for both engineering professionals and general readers.